A destilação reativa na produção do acetato de etila: análise e viabilidade - Mariz, Paulo Romero de Araujo (2021)
This work aims the analysis and feasibility study of the reactive distillation column in the ethyl acetate (EtOAc) production. The esterification reaction of acetic acid (AcOH) with ethanol (EtOH) catalyzed by sulfuric acid is the main commercial route for its production. This technology makes it possible to separate mixtures while a reaction takes place. The advantage is increased reduction and elimination of reactive azeotropes. For analysis, modeling and simulation of the system in the Matlab® environment was performed to solve the set of differential-algebraic equations of the liquid-vapor equilibrium model and residual curves map. For feasibility, the equilibrium constant, the Damköhler number and the residence time are used as criteria. The results obtained allowed for a better understanding of the critical points of the system and the regions that should be avoided during the separation process. The variation in the Damköhler number, 0.05 to 5, evidenced the propagation of the chemical reaction in the quaternary system as well as the change in the composition profiles direction and the minimum boiling point azeotrope displacement (EtOH-EtOAc- H2O). The similarity between boiling temperature of the azeotropes EtOAc-EtOH, H2O-EtOAc-EtOH and EtOAc-H2O makes the pressure variation technique unfeasible for misture separation and the presence of three regions in the ternary diagram H2O-EtOAc-EtOH created by residual curve maps makes extractive distillation unfeasible as well. Therefore, from the ternary diagram and liquid-liquid equilibrium curve, it is clear the ihe importance of recycling water at the top of the distillation column to increase EtOAc purity as well as the need for the feed streams to be equimolar.